Buka pakeṭa, phārsṭa iniṃsa - Senagupta, Priẏama (Dya Kāphe Ṭebala, 2017)
Humorous articles on the life-style of the people of Kolkata
Humor
Keywords: Bengali wit and humor; Lifestyles; India; Kolkata; Humor